Thinking Like A Scientist: Solving Everyday Problems wtih the Scientific Method - Don K Mak (World Scientific, 2009)
Describes how one can use the scientific method to solve everyday problems. This book illustrates how to exploit the information collected from our 5 senses, how to solve problems when no information is available for the present problem situation, and how to extrapolate our capabilities by seeing a relationship among heretofore unrelated concepts.